Tinjauan Atas Aktivitas Harian Unit Teller Pada Pt Bank Negara Indonesia (Persero) Tbk. Kantor Cabang Utama Cibinong - Ayu Nur Safitri; Edy Safni Rosa; Muhammad Ariffin (Program Vokasi dan LPPM IBI Kesatuan, 2022)
Teller is a part of the organizational unit located in the front office, which provides banking services for customers and/or prospective customers. Tellers are tasked with serving various transactions that will be carried out by customers at the money counter by providing good, fast, and accurate service in accordance with teller service standards. The purpose of this discussion is to find out the daily transaction activities of the teller unit, what obstacles occur at the teller caused by several factors including fatigue factors, internal factors, and external factors, as well as how to solve the teller problems. The review conducted by the author is at PT Bank Negara Indonesia (Persero) Tbk. Cibinong Main Branch Office. The results of the discussion from this review indicate that the teller of PT Bank Negara Indonesia (Persero) Tbk. KCU Cibinong has carried out various daily teller transaction activities properly and in accordance with the Teller Service Standars with the obstacles experienced by tellers can be overcome with solutions carried out by tellers and all staff of PT Bank Negara Indonesia (Persero) Tbk. Main Branch Office Cibinong. Keywords : Teller, Teller Transactions, Teller service standard